2017
DOI: 10.24836/es.v27i50.465
|View full text |Cite
|
Sign up to set email alerts
|

Caracterizando la producción y organización de los mezcaleros en Matatlán, México “Capital mundial del mezcal”

Abstract: Caracterizando la producción y organización de los mezcaleros en Matatlán, México "Capital mundial del mezcal"Characterizing the production and organization of the mezcaleros in Matatlan, Mexico "World capital of mezcal"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
1
4
0
3
Order By: Relevance
“…Socialization significant gap (significant imbalance) could be due the nature of the production process, as interaction is in the family from father to son (Espinosa Meza et al, 2017) and not with other producers or external agents or also, can be due a chaotic climate or coercion in the knowledge dynamic interaction that constrict the socialization (Handzic and Chaimungkalanont, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Socialization significant gap (significant imbalance) could be due the nature of the production process, as interaction is in the family from father to son (Espinosa Meza et al, 2017) and not with other producers or external agents or also, can be due a chaotic climate or coercion in the knowledge dynamic interaction that constrict the socialization (Handzic and Chaimungkalanont, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In another study Espejel , showed the importance of including an articulating an element for promoting the knowledge management in the chain sheep from Villa Victoria Mexico. In another study Espinosa Meza et al (2017), shows the forms of organization and production of mezcal producing units, describing the tacit knowledge as the soul of this millenary practice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta característica puede incidir para la siembra de espadín por parte de los productores. Espinosa et al (2017) Señalan que los pequeños productores de mezcal han perdurado como unidades económicas, por el sentido familiar que los caracteriza ya que muchas veces los integrantes de la familia no perciben un ingreso, debido que no son considerados como empleados lo que propicia que los costos referentes a la mano de obra en la producción de mezcal sean bajos o inexistentes (Cuadro 6).…”
Section: Cosechaunclassified
“…americana) y maguey Sierra Negra (Agave americana var. oaxacensis) (García, 2012;Espinosa et al, 2017).…”
Section: Introductionunclassified